2008
DOI: 10.3102/0002831208321445
|View full text |Cite
|
Sign up to set email alerts
|

Southern Coup: Recruiting African American Faculty Members at an Elite Private Southern Research University

Abstract: Competition for highly qualified African American faculty members among elite universities in the United States remains keen. Two of the most successful research universities at recruiting African American faculty members are located in the Southeast. Employing a conceptual framework grounded in organizational culture and climate literature, in this qualitative study the authors identified sets of tangible, intangible, and non-work-related factors that influenced the decisions of 12 African American faculty me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In their analysis of the reasons universities are successful in recruiting highly qualified Black faculty, Barrett and Smith (2008) found that many of their participants mentioned the importance of mentoring relationships with senior faculty. However, studies show that access to mentoring relationships and professional networks designed to support and enhance faculty success is more limited for URM faculty (Aguirre, Martinez, & Hernandez, 1993; Diggs, Garrison-Wade, Estrada, & Galindo, 2009).…”
Section: Academic Mentorshipmentioning
confidence: 99%
“…In their analysis of the reasons universities are successful in recruiting highly qualified Black faculty, Barrett and Smith (2008) found that many of their participants mentioned the importance of mentoring relationships with senior faculty. However, studies show that access to mentoring relationships and professional networks designed to support and enhance faculty success is more limited for URM faculty (Aguirre, Martinez, & Hernandez, 1993; Diggs, Garrison-Wade, Estrada, & Galindo, 2009).…”
Section: Academic Mentorshipmentioning
confidence: 99%
“…Research that has examined specific universities who are successful in recruiting diverse faculty have indicated that race-specific mentoring and interactions with tenured faculty are vital elements for success (Barrett and Smith 2008;Zambrana et al 2015). Furthermore, ideal mentors demonstrated support for their mentee's research and long-term vision and understood the challenges faced by diverse faculty.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies that examined the role of alienation, marginalization (Turner, 2003), the role of socialization (Alex-Assensoh, 2003;Dixon-Reeves, 2003;Kosoko-Laski et al, 2006). Examining factors that result in the dissatisfaction and leaving of African Americans in the academy should be a top priority because African American faculty in higher education promotes academic excellence as well as a critical aspect for advancing academic enterprises (Barrett & Smith, 2008). Although White faculty may be polite and friendly with African American colleagues, at the same time, they can devalue the work of African Americans, provide only casual mentoring, challenge intellectual and pedagogical abilities, and minimize and dismiss their views, perspectives (Alexander &Moore, 2008), andscholarship (Nieman, 2003).…”
Section: African American Faculty At Pwismentioning
confidence: 99%